Soot Modeling of Ethylene Counterflow Diffusion Flames. Issue 9 (2nd September 2019) - Pejpichestakul, Warumporn; Frassoldati, Alessio; Parente, Alessandro; Faravelli, Tiziano
ABSTRACT: Combustion-generated nanoparticles cause detrimental effects to not only health and environment but also combustion efficiency. A detailed kinetic mechanism employing a discrete sectional model is validated using experimental data obtained in laminar counterflow diffusion flames of ethylene/oxygen/nitrogen. Two configurations, named Soot formation (SF) and soot formation/oxidation (SFO) flames, are modeled using one-dimensional simulations. Radiative heat losses reduce the maximum flame temperature in the range of 20–60 K and therefore reduce soot volume fraction by ~ 10%. The model predictions accounting for the radiation effects are quite satisfactory. The model can reproduce the qualitative trends of soot volume fraction peaks that are slightly shifted toward the oxidizer zone with the increased oxygen content. In SF flames, the model predicts the maximum soot volume fraction quite well with the largest discrepancy of two folds. The particle stagnation locations can be reproduced by the model, although they are slightly shifted toward the oxidizer nozzle by ~ 0.4 mm. In SFO flames, the most considerable discrepancy is observed at the least sooting flame (xF, o = 0.23) in which the model over-predicts the maximum soot volume fraction by a factor of two. The effect of soot oxidation is important. The model shows that neglecting oxidation of soot significantly increases soot volume fraction in SFO flames by two folds while SF flames are only marginally affected. Also, ignoring soot oxidation leads to the presence of soot particles in the oxidizer zone where they are not observed experimentally. OH is the most effective oxidizer because the sooting zone is located inside the flame region. The effect of thermophoresis is also investigated. It strongly influences SFO flames due to the high temperature gradient. The model accounting particle diffusivities from Stokes–Cunningham correlation can better characterize the distinct particle stagnation plane of SF flames due to their low diffusion coefficients.